Early-Life Origins of Metabolic Syndrome: Mechanisms and Preventive Aspects - Chien-Ning Hsu (MDPI AG, 2021)
One of the leading global public-health burdens is metabolic syndrome (MetS), despite the many advances in pharmacotherapies. MetS, now known as “developmental origins of health and disease” (DOHaD), can have its origins in early life. Offspring MetS can be programmed by various adverse early-life conditions, such as nutrition imbalance, maternal conditions or diseases, maternal chemical exposure, and medication use. Conversely, early interventions have shown potential to revoke programming processes to prevent MetS of developmental origins, namely reprogramming. In this review, we summarize what is currently known about adverse environmental insults implicated in MetS of developmental origins, including the fundamental underlying mechanisms. We also describe animal models that have been developed to study the developmental programming of MetS. This review extends previous research reviews by addressing implementation of reprogramming strategies to prevent the programming of MetS. These mechanism-targeted strategies include antioxidants, melatonin, resveratrol, probiotics/prebiotics, and amino acids. Much work remains to be accomplished to determine the insults that could induce MetS, to identify the mechanisms behind MetS programming, and to develop potential reprogramming strategies for clinical translation.